Desenvolvimento de um sistema embarcado para realização de manejo de irrigação - Cunha, Marcelo Machado (2019)
Irrigation management is one of the main factors affecting the development of crops, since they are sensitive to both the deficit and excess water. Since irrigated agriculture has been responsible for a large share of the freshwater consumed on the planet, efficient irrigation systems and the use of accurate methods are needed to quantify the water needs of crops so that there is no waste. Irrigating properly favors the reduction of water and electricity use and results in a lower incidence of diseases, since most Brazilian farmers use irrigation excessively. In addition, management is associated with preservation of the environment, allowing sustainable benefits to irrigated agriculture. Given this context, the present work aimed to develop an embedded system for decision making in irrigation processes, aiming at the economics of water resources and electric energy. For this, an automatic meteorological station composed of the five sensors required to calculate the water demand (wind velocity, precipitation, solar irradiance, temperature and relative humidity) was designed and developed, the Penman-Monteith method was used estimation of reference evapotranspiration. After the development of the equipment, the calibration of the sensors was performed, finding determination coefficients (R²) of 0.965; 0.989; 0.989; 0.990, for solar radiation sensors, temperature, relative humidity and wind speed, respectively. For precipitation, a maximum error of 5% was found to be satisfactory. Next, the equipment was evaluated for its functionality in calculating the evapotranspiration of the crop and the management of the irrigation system. The embedded system proved to be reliable and efficient, so no problems were found. The cost of the equipment developed was around $ 270, which corresponds to 7% of the value of an automatic weather station, allowing its acquisition by low-income farmers, as is the case of the farmers in the Irrigated Perimeter of Ribeira. These farmers were trained in the use of this technology and 87% were interested in using the proposed system.